2014
DOI: 10.1016/j.drugalcdep.2014.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of smoking and decision-making behaviors with transcranial direct current stimulation in tobacco smokers: A preliminary study

Abstract: Background Most tobacco smokers who wish to quit fail to reach their goal. One important, insufficiently emphasized aspect of addiction relates to the decision-making system, often characterized by dysfunctional cognitive control and a powerful drive for reward. Recent proof-of-principle studies indicate that transcranial direct current stimulation (tDCS) over the dorsolateral prefrontal cortex (DLPFC) can transiently modulate processes involved in decision-making, and reduce substance intake and craving for v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
121
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(139 citation statements)
references
References 42 publications
12
121
4
Order By: Relevance
“…Two studies [23,24] used an electrode protocol with the anode on the left dlPFC and the cathode on the right dlPFC. In contrast, using the reversed placement of electrodes, a study [25] also reported positive tDCS effects on smoking-related behaviors.…”
Section: Evidence Supporting Tdcs As a Treatmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Two studies [23,24] used an electrode protocol with the anode on the left dlPFC and the cathode on the right dlPFC. In contrast, using the reversed placement of electrodes, a study [25] also reported positive tDCS effects on smoking-related behaviors.…”
Section: Evidence Supporting Tdcs As a Treatmentmentioning
confidence: 97%
“…In another study, Fecteau et al attempted to modulate the decisionmaking behavior of smokers via stimulation over the same cortical region. They showed not only a four-day decrease in the number of cigarettes consumed after anodal stimulation but also more rejections of cigarettes but not monetary offers in an Ultimatum Game [25]. Besides the dlPFC, the fronto-parieto-temporal association area has also been proposed as an accessible stimulation site for modulating smoking-related behaviors [26].…”
Section: Evidence Supporting Tdcs As a Treatmentmentioning
confidence: 99%
“…For addiction studies using tDCS modulation, cigarette consumption was measured for two five-day tDCS applications (active or sham). In smokers, active tDCS (right anodal/left cathodal tDCS to the DLPFC) significantly decreased the number of cigarettes smoked compared to sham stimulation and the effects were maintained for 4 days [17]. Boggio et al [6] applied tDCS to the DLPFC (left anodal/right cathodal tDCS, right anodal/left cathodal tDCS, or sham tDCS) to chronic marijuana users in their study.…”
Section: Tdcsmentioning
confidence: 99%
“…In summary, tDCS influences and modulates risk-taking behaviors [5,12,18,19,47,82,83], choice modulation [46], delayed discounting [30], maladaptive decisionmaking [81], probabilistic guessing [29], moral judgment [37], sunk-cost effect [4], exploration-exploitation trade-offs [61], decision-making and cognitive impulse control [42], perception of space and time [79], dual-task performance [22], model-based learning [70], addiction [6,17,26,60,80], food craving [23,35], and perceptual decision-making [34].…”
Section: Tdcsmentioning
confidence: 99%
“…They applied anodal tDCS to the left dorsolateral prefrontal cortex and cathode to the right supra-orbital area for 20 min with a current intensity of 2.0 mA [116] . Fecteau et al [117] rated two five-day tDCS regimens (active or sham). Stimulation was delivered over the right DLPFC at a 2 mA during 30 min in twelve adults.…”
Section: Alcoholmentioning
confidence: 99%